New selachian records from the Upper Cretaceous of southern Patagonia: Paleobiogeographical implications and the description of a new taxon - Bogan, Sergio; Agnolin, Federico; Novas, Fernando Emilio (Journal of Vertebrate Paleontology)
We describe isolated shark teeth collected in levels of the Calafate Formation (Maastrichtian, Late Cretaceous) on the southeast coast of Argentino Lake, Calafate City, Santa Cruz Province, Argentina. The teeth belong to the hexanchiform Notidanodon dentatus, a new species of the squaliform Protosqualus, and an indeterminate species of the echinorhiniform genus Echinorhinus. The record of Notidanodon constitutes the first in South America. The report of Notidanodon associated with plesiosaur remains is in accordance with previous records from around the world. Protosqualus argentinensis, nov. Sp., which is the first record of the genus in South America, is characterized by having teeth with a apicobasally tall root and serrated cutting edges, among other features. Echinorhinus sp. constitutes one of the oldest records of this genus on the continent and one of the few Mesozoic records worldwide. This shark association is clearly distinct from coeval selachian faunas from northern Patagonia, which exhibit clear Tethyan influences. Instead, it shows some similarities to other high-latitude selachian faunas, including Australia, New Zealand, and Antarctica. It is possible that the Cretaceous selachian assemblages of Patagonia may be separated into two different associations: northern Patagonian faunas are related to more temperate associations of lower paleolatitudes, whereas those of southern Patagonia are closer to other southern localities. Fil: Bogan, Sergio. Universidad Maimonides; Argentina Fil: Agnolin, Federico. Universidad Maimonides; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina